Hantavirus reservoir hosts associated with peridomestic habitats in Argentina - Calderón, Gladys (1999)
Five species of sigmodontine rodents have been identified in Argentina as the putative reservoirs of six circulating hantavirus genotypes. Two species of Oligoryzomys are associated with the genotypes causing hantavirus pulmonary syndrome, Oligoryzomys flavescens for Lechiguanas and O. longicaudatusfor Andes and Oran genotypes. Reports of human cases of hantavirus pulmonary syndrome prompted rodent trapping (2,299 rodents of 32 species during 27,780 trap nights) at potential exposure sites in three disease-endemic areas. Antibody reactive to Sin Nombre virus was found in six species, including the known hantavirus reservoir species. Risk for peridomestic exposure to host species that carry recognized human pathogens was high in all three major disease-endemic areas.